Phytochemical Screening of Essential Oils and Antibacterial Activity and Antioxidant Properties of Barringtonia asiatica (L) Leaf Extract - Isaac John Umaru; Fasihuddin A. Badruddin; Hauwa A. Umaru (Biochemistry Research International)
Objective. To ascertain the essential oil phytochemicals of the leaf and to test for the antibacterial and antioxidant properties of dichloromethane crude extract of Barringtonia asiatica leaf. Methods. The phytochemical screening of essential oils, extraction by hydrodistillation using the Clevenger apparatus, and analysis performed by gas chromatography equipped with a flame ionization detector (GC-FID). Antibacterial activity and the inhibition rate (mm) were determined using the agar disc method against four bacterial strains using tetracycline as positive control. The antioxidant potential of dichloromethane crude extract was investigated spectrophotometrically using 1,1-diphenyl-2-picrylhydrazyl. Results. The essential oil properties were reasonable with major phytochemicals like uncineol 30.9%, eicosane 27.4%, eicosane 21.6%, and 4-propyl-guaiacol 14.05%. The antibacterial activity of the dichloromethane crude extract showed broad-spectrum activity against Salmonella typhi, Escherichia coli, Staphylococcus aureus, and Klebsiella pneumoniae with inhibition value ranges between 2.50 ± 0.10 mm and 5.00 ± 0.06 mm. The dichloromethane crude extract exhibited strong antioxidant activities when compared to the standard. Conclusions. These results suggest that the leaves of Barringtonia asiatica is composed of essential compound as well as antibacterial and antioxidant properties from the crude extract; these are possible due to the presence of some bioactive compounds in the crude extract. The species also showed a reasonable amount of natural products in the essential oils from the hydrodistillation which can as well be used in the cosmetics and food industries.